What critical thinking and for what? - Indrašienė, Valdonė; Jegelevičienė, Violeta; Merfeldaitė, Odeta; Penkauskienė, Daiva; Pivorienė, Jolanta; Railienė, Asta; Sadauskas, Justinas; Valavičienė, Natalija (Social Welfare: Interdisciplinary Approach, 2019)
The article discusses the construction of the critical thinking concept in higher education and its change in scientific publications between 1993 and 2017. Based on a systematic literature review, the following research questions are raised: how does construction of critical thinking concept change in the context of higher education during time? How are personal, interpersonal, and social aspects expressed in the concept of critical thinking in the context of higher education? The systematic literature review revealed significant grow of publications starting from 1998.  It is also disclosed slight change in treating critical thinking as purely general or domain-specific competence. The authors of the researched articles do not make clear division between critical thinking as a general and as a domain-specific competence. Researchers in different fields tend to associate critical thinking with the development of a person’s cognitive and intellectual capacities, including skills and attitudes. However, some authors reveal also interpersonal and social aspects of critical thinking. Alas, there are not so many publications in favour of such comprehensive approach. But there is still some hope that critical thinking will be treated and nurtured as personal, interpersonal and social competence.
Keywords: critical thinking; higher education; social welfare; a systematic literature review